Talking Past Each Other: Government, Business and Civil Society Discussing Cyber Security - M. Finnemore (MGIMO University Press, 2019)
Martha Finnemore has visited MGIMO-University this September, she gave several public lectures for students and participated in a number of roundtables. Professor Finnemore was very kind to give an interview to our journal on various issues of international information and cybersecurity. The interview was conducted by Elena Zinovieva, vice director of the Center for International Information Security, Science and Technology Policy at MGIMO-University.